HOW WE CAN BRING THE CHANGE IN SOCIETY USING ECO-FRIENDLY TECHNOLOGY - Kulkarni, Pranjali (International Journal of Research -GRANTHAALAYAH, 2015)
As the technology develops and becomes widely acceptable, what is eco-friendly technology is a question that many people will be able to easily answer. However, time is need while often more researched need for monitoring the progress. There are some simple day to day things which we can do and become eco-friendly without using the high technology products. If your day-to-day actions are more environmentally-friendly you may not only help the environment, but you can benefit financially, physically and mentally as well. For example, getting rid of toxic chemicals in your home and using natural cleaners will cost less, it will cut down on the number of toxins you are exposing yourself and the environment to and it will have a more positive impact on your indoor air quality. Hence going green is the new way to satisfy your needs, and now that the eco-friendly minds and products get their much awaited attention, this is the perfect time to bring insomeeco-friendly techniques in our daily life to make our mother earth clean and a place to live in.